Upaya Penegakan Hukum dalam Pemberantasan dan Penanggulangan Tindak Pidana Narkoba oleh Kepolisian Polres Kota Gorontalo - Sofyan Hardiyanto Abubakar; Ibrahim Ahmad; Marten Bunga (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Drug cases in Indonesia are at a very worrying level. The phenomenon of abuse of narcotics, psychotropic drugs, and illegal drugs (narcotics), should be a concern for the government and all levels of society in general. The rampant behavioral deviations of the younger generation, namely the occurrence of narcotics crimes, one of which is the abuse of narcotics and illegal drugs, are currently increasing. Teenagers are very potential targets for the circulation of narcotics and dangerous drugs, so there must be real efforts to prevent and eradicate them. The problem approach method used in this writing is the normative legal method. Primary data collection techniques are obtained by conducting searches, inventories and reviewing regulations using literature studies including laws and regulations, books and articles in journals and scientific works. The police in eradicating drug crimes have the authority in accordance with the mandate of Law Number 35 of 2009 concerning Narcotics and Law Number 2 of 2002 concerning the Police. The main authority includes investigation of Pre-emptive, Preventive, Repressive action.